The Influence of Social Class on University Students' Prosocial Behavior Based on the Game Perspective. (13th April 2021) - Ding, Hao; Xu, Feng; Zhu, Jia-Ming
Abstract : In the present research, based on the game research paradigm, the research tools are the dictator game and the trust game, and the research objects are Chinese university students. We adopt 2(self-social class: high, low) × 2(target social class: high, low) between-subjects design experiment to investigate the influence of social class on university students' prosocial behavior. Across the experimental study, we find that (1) in the two situations of dictator game and trust game, self-social class has no significant influence on university students' prosocial behavior; (2) in the situation of dictator game, target social class has a significant influence on university students' prosocial behavior, and it is regulated by self-social class. Under the condition of low self-social class, the higher the target social class, the more prosocial behavior of university students, which confirms the perspective of status and negates "if you are poor, you will be good for yourself." Under the condition of high self-social class, the lower the target social class, the more prosocial the behavior of university students, which confirms the perspective of fairness and echoes "if you are good, you will be good at the world"; (3) in the context of the trust game, target social class has a significant influence on university students' prosocial behavior, and there is no interaction effect with self-social class.